2015
DOI: 10.5603/piap.2015.0076
|View full text |Cite
|
Sign up to set email alerts
|

Selected Molecular Events in the Pathogenesis of Sarcoidosis—Recent Advances

Abstract: Sarcoidosis is an orphan inflammatory disorder that can virtually affect any organ or system in the body, although the lungs and lymph nodes are most frequently involved. Sarcoidosis is believed to derive from an interaction between environmental and genetic agents. Many studies emphasize a strong association between certain human leukocyte antigen (HLA) alleles and sarcoidosis susceptibility. Several new insights have allowed the further evaluation of other candidate genes with a potential function in the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 128 publications
(163 reference statements)
0
4
0
3
Order By: Relevance
“…There is not much documentation for this association. The inflammation in sarcoidosis is similar to CD; granulomatous; Th1 and 17 driven; and mutations in NOD2 and IL 23 receptor gene are identified[ 2 , 69 - 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is not much documentation for this association. The inflammation in sarcoidosis is similar to CD; granulomatous; Th1 and 17 driven; and mutations in NOD2 and IL 23 receptor gene are identified[ 2 , 69 - 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of sarcoidosis remains highly elusive, it is conventionally believed to derive from an interaction between environmental antigens and genetic factors (the genetic–environmental theory). 13 ACCESS, a US-based multicenter epidemiologic study of 706 clinically and histologically confirmed subjects with sarcoidosis, failed to identify a single predominant environmental, infective, or occupational “cause” of sarcoidosis. 14 This large case–control study suggests that multiple environmental sources of exposure may trigger an aberrant immunomediated granulomatous response in genetically susceptible individuals.…”
Section: Pathogenesis and Geneticsmentioning
confidence: 99%
“… 18 , 19 There appears to be a strong association between certain human leukocyte antigen (HLA) alleles and sarcoidosis susceptibility and disease behaviour. 12 , 13 Both HLA class I and II human leukocyte antigens have been implicated, with HLA class II genes reported to be more strongly and consistently associated. Certain alleles, such as HLA-DRB1 (HLA-DRB1*11, *12, *14, *15) are principally correlated with susceptibility, disease phenotype, and prognosis.…”
Section: Pathogenesis and Geneticsmentioning
confidence: 99%
“…The peak age of onset is between the second and the fourth decades of life. The incidence of sarcoidosis in Poland is estimated at approximately 10 cases per 100 thousand citizens (the worldwide incidence is 1-64/100 000; the highest incidence is observed in Scandinavian countries and among Afro-Americans in the USA, while the lowest is found in Singapore and Japan) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%